Permeability of ambient cured fly ash geopolymer concrete blended with additives - Nath, P.; Sarker, Prabir (RILEM Publications S. A. R. L, 2016)
Fly ash geopolymer concrete is a low-emission alternative building material to ordinary Portland cement (OPC) concrete. Previous studies mostly reported the properties of heat cured geopolymer concrete. However, heat curing is a costly and energy-intensive process which is not always feasible for cast-in-situ concreting. This study presents the effects of different mixture parameters on the permeability properties of geopolymer concrete cured in ambient condition. Low-calcium fly ash was blended with small percentages of additives such as blast furnace slag, OPC and hydrated lime in order to enhance setting and overcome the need for heat curing. The results of different mixtures were compared with those of control geopolymer and OPC concrete. The results of ambient cured geopolymer samples were also compared with those of heat cured samples. It was found that the volume of permeable voids (VPV) of geopolymers modified with different additives remained unaffected, despite achieving higher strength as compared to the control concrete. Sorptivity of the mixtures depended on the type and amount of the additives present in the mixture. The results suggest the possibility of developing suitable blends for ambient-cured geopolymer mixtures to achieve similar strength and permeability properties as those of OPC concrete and heat-cured geopolymer concrete.